2022
DOI: 10.1186/s12885-022-10046-z
|View full text |Cite
|
Sign up to set email alerts
|

Validating ORR and PFS as surrogate endpoints in phase II and III clinical trials for NSCLC patients: difference exists in the strength of surrogacy in various trial settings

Abstract: Objective This study aims to systematically validate the performance of surrogate endpoints in phase II and III clinical trials for NSCLC patients under various trial settings. Methods A literature search retrieved all registered phase II and III trials of NSCLC patients in which OS, with at least one of ORR and PFS, were reported. Associations between surrogate and true endpoints were assessed on two levels. On the arm level, three pairs of correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Indeed, the relationship between PFS and OS is complex and varies across different cancer types and therapeutics. In the context of NSCLC and immunotherapy or targeted therapies, previous studies suggest, at most, moderate potential for PFS to be used as a surrogate of OS (Ye et al 2020 ; Shameer et al 2021 ; Hua et al 2022 ), while strongly advocating for the need for patient-level analyses, where true surrogacy can be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the relationship between PFS and OS is complex and varies across different cancer types and therapeutics. In the context of NSCLC and immunotherapy or targeted therapies, previous studies suggest, at most, moderate potential for PFS to be used as a surrogate of OS (Ye et al 2020 ; Shameer et al 2021 ; Hua et al 2022 ), while strongly advocating for the need for patient-level analyses, where true surrogacy can be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…ORR was selected as the primary end point for this single‐arm study. Some evidence has suggested that, in phase 2 studies evaluating immune checkpoint inhibitors, ORR may not correlate with PFS and OS and underestimate clinical benefit 25,26 . Prior studies of targeted therapies in patients with thyroid cancer have reported 2‐year OS rates of approximately 60% 3,4,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis of NSCLC patients has been improving with continuing breakthroughs in research into driver genes and the availability of several new therapeutic options [15][16][17]. However, rapid drug resistance due to tumor heterogeneity is also creating new challenges in NSCLC [18,19].…”
Section: Discussionmentioning
confidence: 99%